Children exposure to inorganic and organic arsenic metabolites: A cohort study in Northeast Italy. (October 2020) - Bocca, Beatrice; Pino, Anna; Brumatti, Liza Vecchi; Rosolen, Valentina; Ronfani, Luca; D'Aversa, Jenny; Ruggieri, Flavia; Petrucci, Francesco; Calamandrei, Gemma; Barbone, Fabio; Alimonti, Alessandro
Abstract: The aim of this study was to provide urinary levels of total arsenic (TAs) and As species as arsenobetaine (AsB), arsenocholine (AsC), inorganic As (i.e., [As(III)+As(V)]), methylarsonic acid (MMA) and dimethylarsinic acid (DMA) in 7 year-old-children (n = 200) enrolled in the Northern Adriatic Cohort II (NACII), a prospective cohort in a coastal area of Northeast Italy. TAs was determined by sector field-inductively coupled plasma mass spectrometry (SF-ICP-MS) and AsB, AsC, As(III), As(V), MMA and DMA by ion chromatography coupled to ICP-MS (IC-ICP-MS). The geometric mean (GM) for TAs was 12.9 μg/L and for [iAs + MMA + DMA] was 4.26 μg/L. The species AsB (GM of 5.09 μg/L) and DMA (GM of 3.20 μg/L) had the greatest percentage contribution to TAs levels; a greater percentage contribution from AsB is seen at TAs >10 μg/L and from DMA at TAs <10 μg/L. Urinary [iAs + MMA] levels were positively associated with [iAs + MMA + DMA] and DMA with AsB levels. Fish, shellfish and crustaceans consumption increased the AsB and TAs levels, while rice intake, mothers' education level and selenium (Se) concentration influenced the DMA concentration. Children have a high capacity to metabolize and detoxify the iAs because of the higher secondary methylation index (ratio DMA/MMA) with respect to primary methylation index (ratio MMA/iAs). In addition, the median level of [iAs + MMA + DMA] in the whole population of children was lower than the Biomonitoring Equivalent (BE) value for non-cancer endpoints. Also the Margin of Safety (MOS) value based on the population median was greater than 1, thus the exposure to the toxicologically relevant As species was not likely to be of concern. Graphical abstract: Image 1 Highlights: Urinary As, arsenobetaine (AsB), arsenocholine (AsC), As(III), As(V), methylarsonic acid (MMA) and dimethylarsinic acid (DMA). AsB was predominant followed by DMA and then by As(III), while As(V), MMA and AsC were at trace levels. Seafood influenced AsB levels, while rice intake, mothers' education level and selenium (Se) influenced DMA concentrations. Exposure to toxic As - as [iAs + MMA + DMA] - was lower than the Biomonitoring Equivalent (BE) value for non-cancer endpoints. The Margin of Safety (MOS) value as the ratio between the BE and the [iAs + MMA + DMA] was greater than 1. Abstract : Children exposure to arsenic species.